Central metatarsal fractures: a review and current concepts - Samaila, Elena Manuela; Ditta, Alessandro; Negri, Stefano; Leigheb, Massimiliano; Colò, Gabriele; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2020)
Central metatarsal fractures (CMF) are common injuries. More frequently fractures are those of the fifth metatarsal, followed by CMF and therefore by the first metatarsal. Third metatarsal is injured most frequently than the others and up to 63% is associated with second or fourth metatarsal fractures and up to 28% with both. Anatomy and metatarsal kinematics merits attention due to its influence on function, injuries and treatment options. Diagnosis is based on the history of trauma and clinical examination, relating with instrumental exams. Fractures with less than 10° of angulation and 3-4 mm of translation in any plane are typically treated conservatively, while operative treatment is generally reserved for fractures out if these values. Intramedullary fixation with K-wires seem to be the most common and valid surgical treatment in simple fractures. Spiral fractures should be treated by interfragmentary screws, which positioning may result difficult due to the adjacent metatarsals. Therefore, an alternative approach is an osteosynthesis with a dorsal plate. Multiple metatarsal fractures often occur in the contiguous bones, so clinicians will also have to carefully inspect metatarsals and adjacent joints such as Lisfranc articulation. The clinical and functional outcomes are often influenced by the pattern of fractures and patient conditions and are reported in the literature up to 39% of poor results.